The Effectiveness of Using Instagram Application on Students’ Vocabulary Size in Papua Senior High School - Amritha Yuningtyas Harjuni Serang; Rahmawansyah Sahib (KARIWARI SMART : Journal of Education Based on Local Wisdom, 2023)
This study aimed to investigate the effectiveness of using the Instagram application to increase the vocabulary. This research employed an experimental design. The populations were the students of SMA Negeri 1 Sentani in the academic year 2021/2022. The sample consisted of 34 students from grade 11 (19 females and 15 males) chosen by using a purposive sampling technique. The instruments of this research were pre-tests, treatment and post-tests. The data was analyzed by using SPSS for Windows. As per the data, the experimental group experienced improvement in their understanding of using the Instagram application to increase the vocabulary and order indicated by the post-test mean score (84.7). The gain score of the experimental group was (55.7). Another supporting indicator is the t-test value, which was higher than the t-table value (8.379>2.035). The result of this study showed that experimental performance had improved significantly. Which mean null hypothesis (H0) was rejected and alternative hypothesis (Ha) was accepted. As a result, it was determined that the Instagram application was effective in increasing the size of students' vocabulary. The author suggests that more research be completed on using Instagram as a teaching tool to improve students' four skills: listening, reading, speaking, and writing.